OM 4 (Operation management) - Collier, David A.; Evans, James R. (Mason, Ohio : South-Western Cengage Learning, 2013)
"A student-tested, faculty-approved approach to teaching and learning operations management; demonstrate core concepts with company cases & profiles; plus, a full suite of instructor supplements."-
Goods, services, and operations management -- Value chains -- Measuring performance in operations -- Operations strategy -- Technology and operations management -- Goods and service design -- Process selection, design, and analysis -- Facility and work design -- Supply chain design -- Capacity management -- Forecasting and demand planning -- Managing inventories -- Resource management -- Operations scheduling and sequencing -- Quality management -- Quality control and SPC -- Lean operating systems -- Project management.
Keywords: PRODUCTION MANAGEMENT